PEMANFAATA N EKSTRAK DAUN WUNGU Graptophyllum pictum (L.) Griff. UNTUK PENURUNAN KADAR KOLESTEROL SERUM DARAH MENCIT BETINA YANG DIOVARIEKTOMI - Listijani Suhargo (The East Java Biological Society, 2008)
The purpose of this research was conducted to evaluate the effects of “daun wungu” extracts to decrease total cholesterol, LDL (Low Density Lipoprotein) and HDL (High Density Lipoprotein) cholesterol of ovariectomized mice. This research used 24 ovariectomized mice and 8 normal mice. The ovariectomized mice were grouped in 3 groups for K1 (the treatment with aquadest, 0.05 ml), K2 (the treatment with fish oil, 0.05 ml) and P (the treatment with “daun wungu” extracts, 0.5 mg in 0.05 ml fish oil). All treatments were done for 20 days. At the end of the treatments, the blood (0.5 ml) was taken from cardiac by tuberculin disposable syringe. And then with fotometry, serum total, LDL and HDL cholesterol were measured. The result of this research showed that daun wungu extracts (0.5 mg in 0.05 ml fish oil) could not decrease HDL cholesterol, but it could decrease total and LDL cholesterol of blood serum in ovariectomized mice.